Algorithmic foundations for the study of electromagnetic processes in the electric drive of a sealed valve - K.K. Kim; Ivanov S. N.; Azimov Kh. Kh. (Российская Арктика)
An algorithm for studying electromagnetic processes in the drive of a sealed valve operated at low temperatures is considered. The possibility of installing an additional element between the stator and rotor of the drive electric motor that performs the functions of sealing and heating is shown.